Effects of interpretation bias modification on unregulated and regulated emotional reactivity. (September 2019) - Van Bockstaele, Bram; Notebaert, Lies; Salemink, Elske; Clarke, Patrick J.F.; MacLeod, Colin; Wiers, Reinout W.; Bögels, Susan M.
Abstract: Background and objectives: Although induced changes in interpretation bias can lead to reduced levels of stress reactivity, results are often inconsistent. One possible cause of the inconsistencies in the effects of interpretation bias modification (IBM) on stress reactivity is the degree to which participants engaged in emotion regulation while being exposed to stressors. In this study, we distinguished between the effects of IBM on natural, unregulated stress reactivity and the effects of IBM on people's ability to up- or downregulate this stress reactivity. Method: Both in the context of general anxiety (Experiment 1, N = 59) and social anxiety (Experiment 2, N = 54), we trained participants to interpret ambiguous scenarios in either a positive or a negative manner, and we assessed the effects on unregulated and regulated stress reactivity. Results: Although we found relatively consistent training-congruent changes in interpretation bias in both experiments, these changes had no effect on either unregulated or regulated stress reactivity. Limitations: In both experiments, we used healthy student samples and relatively mild emotional stressors. Conclusions: In line with previous research, our findings suggest that the effects of IBM on unregulated stress reactivity may be small and inconsistent. Differences in the extent to which participants engaged in emotion regulation during stressor exposure are unlikely to account for these inconsistencies. Highlights: Interpretation Bias Modification (IBM) inconsistently affects stress reactivity. We assessed effects of IBM on both regulated and unregulated stress reactivity. Scenario IBM resulted in training-congruent changes in interpretation bias. IBM had no effects on either regulated or unregulated stress reactivity. In line with other null-results, we show that IBM does not affect stress reactivity.